Chemically induced morphing in polyurethane shape memory polymer micro fibers/springs - Wang, Chang Chun (2013)
Chemically induced morphing in polyurethane shape memory polymer (SMP) micro fibers/springs was investigated experimentally and theoretically. It was revealed that at the presence of water/ethanol, the release of the residual strain/stress (captured during the fabrication process of micro fibers/springs from melted polyurethane SMP) is the driving force for morphing (by means of self-winding and self-twisting/untwisting). A theoretical model was developed to explain the underlying mechanisms behind all types of observed morphing phenomena.